Geología del cuaternario y ciencia del suelo : Relaciones geomórficas-estratigráficas con suelos y paleosuelos - Súnico, Alejandro (1996)
In the northeastern area of Chubut province (Patagonia-Argentine) were studied the existing relationship among geoforms and soils and paleosoils that on them evolved. These last were analyzed from a stratigraphic point of view using their most important macromorphological characteristics. Carbonatic accumulations (Calcretes) are the most significant feature of Cenozoic deposits (Rodados Patagonicos). Crust structures, consistences, thicknesses and other sedimentary and pedologic characters and his association or not to cryogenic structures are used us stratigraphic and morphostratigraphic markers. Several depositational levels of Rodados Patag—nicos were determined through of the analysis of aerial photographs, NOAA, LandSat - MSS and ERS-1 magnetic records integrated to edaphic, paleopedologic and sedimentary information of the deposits and digital topographic information. These levels are corresponded with several fluvial terrace levels, pediments and another minor forms. In most cases these geoforms posses a set of sedimentary and pedologic features that identify them. The general aim of this thesis is establish the dynamic and evolution of the Quaternary continental environment through the characterization of space--temporary existing relationship among forms and soils, paleosoils and deposits.